Rural Health Services: Data, technology and the social capital of local health professionals, time to invest! - David S Briggs (ACHSM, 2019)
Recent editorials have had some focus on health policy and health reform and included commentary about the variability of output from public policy research institutes, based on their respective philosophical and ideological position. Recently, a group Global Access Partners (GAP) published a report entitled 'Australia's Health 2040: GAP Taskforce Report'. [1] This organisation is said to be an independent non-profit institute, established in 1997 and is a member of the TCG Group, described as a diverse and growing network of Australian-owned companies. [1,2].....